Accelerating Regional Development of the Outer Islands: The Implementation of Special Economic Zones in Indonesia, 2011–18 - Siregar, Yani Parasti (2021)
Economic development efforts in Indonesia have long focused on Java, home to more than half of Indonesia’s population, which has exacerbated disparities with the outer islands. To address the issue, the Indonesian government established a number of special economic zones (kawasan ekonomi khusus) in 2011. Efforts to promote business development within the zones faced two challenges: inadequate infrastructure and burdensome government rules and procedures. In response, the government established administrators as integrated one-stop service centers to manage all necessary business activities. Central and local governments also worked together with special economic zone operators to build critical infrastructure to connect local resources to global markets. These policies helped drive more economic activities in the special economic zones, though, as of 2020, further efforts were necessary to address unequal regional development across Indonesia.
Keywords: Decent Work and Economic Growth; Unsupportive Legal or Regulatory Process; Basic Infrastructure